Acute cardiac care : community and hospital management of myocardial infarction - Jennings, Kevin (Oxford medical publications, 1995)
A practical guide to the recognition and management of myocardial infarction and its complications, both in the community and in hospital. Contents: 1. Epidemiology and pathology; 2. Reducing the risk; 3. Unstable Ischaemia; 4. Pre-hospital maangement; 5. Hospital management of mycardial infarction; 6. Complications of myocardial infarction; 7. Recovery; 8. Procedures; 9. Cardiac drugs; References; Index